How Knowledge Sharing Mediates the Effect of Authentic Leadership on Organizational Commitment - Dana Perkasa, I Gede Tito; Rahyuda, Agoes Ganesha (International Research Journal of Business Studies, 2024)
This study aims to provide empirical evidence of the effect of Authentic Leadership on Organizational Commitment which is mediated by Knowledge Sharing. This research is causality associative research using a quantitative approach. The scope of this research includes the subject of the research, namely permanent employees and contract employees at PT. Karya Pak Oles Tokcer who work in Bali Province. The population in this study were all employees of PT Karya Pak Oles Tokcer in Bali Province with a total of 117 employees. The sampling technique used in this study was saturated sampling which is included in non-probability sampling. The data analysis technique in this study uses two analysis techniques, namely descriptive statistical analysis and inferential statistical analysis using Structural Equation Modeling (SEM). The results of the analysis provide evidence that Authentic Leadership has a positive effect on Organizational Commitment and Authentic Leadership affects Knowledge Sharing. Knowledge Sharing also has a positive effect on Organizational Commitment and mediates Authentic Leadership on Organizational Commitment.